2018
DOI: 10.7150/ijbs.26776
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of autophagy and Nrf2 signaling augments bortezomib-induced apoptosis by increasing ROS production and ER stress in pancreatic cancer cells

Abstract: Pancreatic cancer (PC) is highly resistant to current therapies; thus, there is an urgent need to develop new treatment strategies. The proteasome is crucially important for proteostasis, which is involved in cell proliferation and survival, making it an attractive therapeutic target in cancer. However, recent studies have indicated that bortezomib, a highly selective proteasome inhibitor, has limited effects in solid tumors including PC. Thus, more mechanistic insights into chemo-sensitization strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…When cells are subjected to strong external environmental stress, the unfolded or misfolded proteins accumulate in the ER, causing ER stress. Many drugs, such as bortezomib 17 , suffruticosa aqueous extracts 32 and apatinib 18 , cause ER stress and then induce apoptosis. Similar to these reports, our study also found that anlotinib induced increases in BiP, PERK and CHOP, which are ER stress biomarker proteins.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…When cells are subjected to strong external environmental stress, the unfolded or misfolded proteins accumulate in the ER, causing ER stress. Many drugs, such as bortezomib 17 , suffruticosa aqueous extracts 32 and apatinib 18 , cause ER stress and then induce apoptosis. Similar to these reports, our study also found that anlotinib induced increases in BiP, PERK and CHOP, which are ER stress biomarker proteins.…”
Section: •−mentioning
confidence: 99%
“…ATF4 then triggers apoptosis via activating CHOP, a promotive apoptosis protein that is involved in cell stress and induces cell cycle arrest 16 . In cancer treatment, ER stress is a common process that many antitumour drugs exploit to induce apoptosis in cancer cells, such as bortezomib 17 and apatinib (a TKI) 18 . Hence, we suspected whether anlotinib has a similar mechanism against PC.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid cell apoptosis is a typical characteristic in the most of cancers. Moreover, cell autophagy and apoptosis were pivotal regulation in the development of cancer, which could result in the severity of canceration [41,42]. Increasing numbers of research has demonstrated that chemotherapeutic and Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial activities, including beta-oxidation of free fatty acids, production of ATP, and ROS are all central to homeostatic regulation of lipid and energy metabolism in hepatocytes (32). In addition, compounds such as ROS are important for the regulation of apoptosis (33). In vitro, compared with OA, exogenous PA led to greater ROS accumulation in rat hepatoma cells, a response partly caused by the inability of mitochondria to handle large amounts of exogenous long-chain fatty acids, which often leads to mitochondrial dysfunction (34,35).…”
Section: Discussionmentioning
confidence: 99%